The impact of customer equity, religious commitment, staying reasons on switching behaviour amongst millennial Muslim consumers in Lahore and Kuala Lumpur / Munazza Saeed - Munazza, Saeed (2017)
The phenomenon of brand switching behaviour is a constant challenge for organizations in today’s competitive and dynamic business environment not only to retain existing consumers but to attract new consumers as well. The theory of planned behaviour and theory of migration were utilized to develop the framework for this study. The impact of following constructs: customer equity, religious commitment, staying reasons, and switching intention, were examined on brand switching behaviour. This study has four research objectives. First, to examine the differences of customer equity, religious commitment, and staying reasons between Lahore and Kuala Lumpur; second, to investigate the effect of customer equity, religious commitment, staying reasons, and switching intention on brand switching behaviour of Muslim consumers; third, to determine the role of switching intention as mediator; and finally, moderating effect of country and gender on brand switching behaviour of Muslim consumers. Fieldwork for this study was carried out on Muslim consumers in Lahore (Pakistan) and Kuala Lumpur (Malaysia). Globally, the Muslim population is growing rapidly and it is projected that it will be nearly twice of the non-Muslim population in the future. Collectively, Muslim consumer has purchasing power and power to speak about brands but they have diverse background with differences in the conformity to religious requirements. The research data was collected by means of quantitative probability sampling (survey questionnaire) and qualitative (interviews). Using survey questionnaire, 706 valid responses were analysed through SPSS and structural equational modelling (SEM) in AMOS. The main quantitative techniques used in SPSS, include exploratory factor analysis and t-test, whereas, quantitative techniques used in AMOS include path analysis, mediation, and multi-group moderation. Qualitative data were analyzed by thematic analysis in Atlas.ti. The results reveal that there were significant differences of customer equity, religious commitment, and staying reason between respondents in Lahore and Kuala Lumpur. Regardless of the difference exist between Pakistani and Malaysian respondents, interestingly, customer equity and staying reasons were effecting the brand switching behaviour whereas, religious commitment was not influencing the brand switching behaviour in both cities. Putting together, although religious commitment does not have much influence on brand switching behaviour of Muslim consumers but staying reasons and customer equity were significantly effecting the brand switching behaviour. Moreover, switching intention mediated the relationships among customer equity, staying reasons, and brand switching behaviour, except religious commitment. Country was a significant moderator, whereas, gender was not playing a significant role on brand switching behaviour, which initiates a new debate about the role of gender.